Mengidentifikasi Faktor Faktor yang Mempengaruhi Malas Belajar pada Siswa SMP: Studi Kasus di Sekolah Menengah Pertama Kelas VIII SMP IT Mutiara Aulia - Asy’ari, Humairoh; Hartady, Alfitrah Boban; Rezky, Annisa; Anggraini, Anggita; Amalia, Syakira (PT. Kreasi Karya Majakata, 2024)
Learning activities are a process of interaction between students and educators which aims to develop intellectual, moral, emotional and maturity aspects. Identify the factors that cause children to be lazy about studying in Sei Mencirim Village, Sunggal District, Deli Serdang Regency, Mutiara Aulia IT Middle School. This research aims to: Find out the causal factors that influence children to be lazy about studying. The research method we use in this research is a qualitative method, what is meant by qualitative research is qualitative research aimed at understanding social phenomena or realities through collecting non-numerical data, such as interviews, observations, and text or document analysis. In the research, it was found that the reasons why students at SMP IT Mutiara Aulia were lazy about studying were, namely, 1) Factors that came from within the child, 2) Factors that came from outside the child which caused the child to be lazy about studying. Based on the results of this research, the researcher provides suggestions, namely: 1) Parents who put their children to study at this school must pay extra attention and provide more attention and motivation, especially in the educational context. 2) For the community, especially community leaders around where students live, they must always provide supportive advice to be given and listened to by students who live in that area so that the child is willing to study hard at school. 3) For teachers, stay enthusiastic, never give up and always be patient in educating students at Mutiara Aulia IT Middle School.